Social Media Transforming Tourist Behavior - İştin, Aysen Ercan (Emerald Group Publishing Ltd., 2020)
The discovery of internet technologies which is one of the most important developments of the twenty-first century has enabled individuals and institutions to overcome geographical and time constraints creating fundamental changes in communication. As a result, online communities have enabled people to meet the internet for various reasons such as seeking and sharing information, discuss community issues and ask questions; and online communities have also enabled businesses and consumers to connect with each other at any time. Especially the emergence of Internet-based social media technologies such as blogs, virtual communities, wikis, social networks, YouTube, Facebook and Instagram provides tourists to share their travel experiences. Information shared on social media sites is considered to be an important source of information that can help tourists’ travel plan and may even influence the travel decisions of potential tourists. In this context, the concept of social media in tourism businesses has been examined in the research. Within the framework of the research, it has been observed that social media has influenced the tourists’ behavior regarding travel motivations in the context of various motivations (having information about destinations, hotels, services of hotels, wondering about consumers’ experiences who were in touristic consumption before, etc.). It is also among other findings that social media has increased the overtourism crisis. © 2021 Emerald Publishing Limited.
Keywords: Consumer experience; Internet technology; Social media; Tourism businesses; Tourist behavior; Travel motivation